Avaliação do Projeto de Desenvolvimento do Ecoturismo na Mata Atlântica em parques do estado de São Paulo - Kaneshiro, Daniela Midori (2014)
The Atlantic Rainforest, which has the title of World Heritage by UNESCO, is a very important area that must be preserved for its rich biodiversity, in addition to the natural and cultural assets that attract tourists. For all these reasons has considerable tourism potential and can contribute to the region's economy. The Design of Development of Ecotourism in the Atlantic Forest region was created to implement actions that benefit the communities surrounding protected areas, as well as broaden the infrastructure for the visitation in order to establish an orderly tourism management to avoid negative impacts on the region. This study aimed to evaluate this project from its conception to the end of their actions in 2012, especially its indicators, applying the methodology PDCA (Plan, Do, Check and Act). In its seven years of implementation and with the constant changes in park management and technical project, it is important to make a study and review of the activities and present the work done. Of 9 indicators, 4 achieved the target and the rest are close to reaching. The increase in the amount of published normative instruments and value in the income earned on the rise present a breakthrough for the Protected Areas. For the Bank, the results were positive; they were paid 98.15% of the total contract value. Moreover, due to the dollar variation, investments were canceled. For managers of parks, the balance was also positive for the gain with environmental education and improvement tools in the infrastructure to receive visitors. The activities carried out in the Project caused the state to be in inducing paradigm change in relation to the parks because: plus space for research, public visitation shall receive investments in order to increase the number of visitors but also improved quality receptive, which causes change in participation around. This change is characterized by a qualified participation of traditional communities, local businesses and the municipal government.